Macromol. Rapid Commun. 11/2015. Issue 11 (2nd June 2015) - Gemünden, Patrick; Poelking, Carl; Kremer, Kurt; Daoulas, Kostas; Andrienko, Denis; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> Back Cover: Predicting the hierarchic structure and charge transport properties of polymeric semiconductors requires simulation techniques that describe mesoscale order while preserving atomistic details. Shown is the hierarchy of coarse‐grained models—from plate‐based to atomistic—used for predictions and sequential refinement of large‐scale morphologies. Further details can be found in the article by P. Gemünden, C. Poelking, K. Kremer, * K. Daoulas, * and D. Andrienko* on page 1047.